Effect of Ethanolic Extract of Moringa oleifera, Lam. Roots on Expression of Cyclin D1 in Testicular Tissue of Metabolic Syndrome Induced Wistar Rats - Sephendra Lutfi; Dyah Ratna Budiani; Novan Adi Setyawan (Indonesian Journal of Medicine, 2023)
Background: Metabolic syndrome (MS) impacts on inhibition process of spermatogenesis by damaging various components of cell cycle proteins. Cyclin D1 protein which plays role in regulating the cell cycle of spermatogenic cells is depleted due to the metabolic syndrome. Variation results of M. oleifera studies on fertility are interesting for further research. This study aimed to determine the effect of ethanolic extract of M. oleifera roots towards expression of testicular cyclin D1 of metabolic syndrome induced Wistar rats.Subjects and Method: This study was an experimental laboratory. Thirty subjects of male Wistar rats were randomly divided into 5 groups consisted of 6 rats, control group (K1), MS group (K2), and treatment groups (K3, K4, and K5) which were given doses of 150, 250, and 350 mg/kgBW, respectively for 28 days. Induction of MS was achieved by high-fat diet for 28 days and injection of streptozotocin-nicotinamide (STZ-NA) on day 25. Cyclin D1 data was calculated using Intensity Distribution Score (IDS) and analyzed using one-way ANOVA test followed by post hoc multiple comparisons with Tukey HSD. Simple liniar regression test conducted on cyclin D1 data of K2, K3, K4, and K5.Results: One-way ANOVA test showed that the administration of ethanolic extract M. oleifera Lam. roots with doses of 150, 250, and 350 mg/kgBW in 28 days increased cyclin D1 significantly (p= 0.000). There were significant differences between K1 and K2 (p= 0.000), K2 and K3 (p= 0.000), K2 and K4 (p= 0.000), K2 and K5 (P= 0.000). Liniar regression test showed significant (p= 0.000) and moderate effect (R2= 0.65) of doses of ethanolic extract of M. oleifera roots on the expression of cyclin D1.Conclusion: The administration of ethanolic extract Moringa oleifera Lam. roots with doses of 150, 250, and 350 mg/kgBW for 28 days increased cyclin D1 in testicular rats.